2020
DOI: 10.1364/prj.381208
|View full text |Cite
|
Sign up to set email alerts
|

Effective suppression of the photodarkening effect in high-power Yb-doped fiber amplifiers by H2 loading

Abstract: The radical suppression of the photodarkening effect and laser performance deterioration via H 2 loading were demonstrated in high-power Yb-doped fiber (YDF) amplifiers. The photodarkening loss at equilibrium was 114.4 dB/m at 702 nm in the pristine fiber, while it vanished in the H 2 -loaded fiber. To obtain a deeper understanding of the impact of photodarkening on laser p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Compared with the improved conventional vapor deposition method, equilibrium PD-induced excess loss of the nanoporous glass fiber was reduced to 35.07, 12.49, and 1.69 dB/m at 702, 810, and 1041 nm, respectively, despite higher Yb 3+ concentration. In 2020, Cao et al [37] found that in high-power YDF amplifiers, H 2 loading could fundamentally inhibit the deterioration of the optical aging effect and laser performance.…”
Section: Research Progress Of Ytterbium-doped Fiber (Ydf) Photodarkeningmentioning
confidence: 99%
“…Compared with the improved conventional vapor deposition method, equilibrium PD-induced excess loss of the nanoporous glass fiber was reduced to 35.07, 12.49, and 1.69 dB/m at 702, 810, and 1041 nm, respectively, despite higher Yb 3+ concentration. In 2020, Cao et al [37] found that in high-power YDF amplifiers, H 2 loading could fundamentally inhibit the deterioration of the optical aging effect and laser performance.…”
Section: Research Progress Of Ytterbium-doped Fiber (Ydf) Photodarkeningmentioning
confidence: 99%
“…For simplicity, the transverse fluctuation (D c ) and cross effect (D c L c ) were used as variables. Finally, the estimation of P th and η is obtained in Equations ( 9) and (10). For the function y = f(x i ), a sensitivity analysis was calculated using Equation (12) to assess the effect of the independent variable x i on the dependent variable y.…”
Section: Laser Performance Estimation Modelingmentioning
confidence: 99%
“…Ytterbium ion (Yb 3+ ) has been widely studied as an optimal gain medium for high-power lasers due to its small quantum defect. [1][2][3][4][5][6][7][8][9][10][11][12] Due to the high Yb 3+ solubility, high gain single-frequency laser can be obtained from a Yb 3+ -doped phosphate fiber with a short linear cavity. 13 Thus, improving the laser performance of phosphate fibers is conducive to the miniaturization and integration of optical devices with linear cavity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Superfluorescent fiber source (SFS), which originates from the superfluorescent radiation in the gain medium of optical fiber, not only has the advantages of fiber lasers such as high efficiency and high beam quality [1,2], but also inherits the merits of superfluorescent sources such as broadband emission and low coherence [3,4], thus showing great application potential in sensing, spectroscopy, biomedical imaging and so on [5][6][7][8]. Compared with fiber oscillators which have well-defined cavities, SFS shows higher temporal stability while maintaining good power scalability [9,10], so it is pretty suitable for pumping the optical parametric oscillators (OPOs) [11,12] and Raman fiber lasers (RFLs) [13,14].…”
Section: Introductionmentioning
confidence: 99%